ANALYSIS OF THE IMPACT OF GIVING REWARDS AND ICE BREAKERS ON THE LEARNING PROCESS AT SDN 04 KARANGTENGAH - Intan Putri Kania; Resnawati Febriani P; Fitria Nurulaeni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
The learning process should be an active activity for students to build their understanding. Even so, there are still many students who look bored and lack enthusiasm. The effort that needs to be done by the teacher is by giving rewards and ice breaker. This study aims to determine the impact of giving rewards and ice breakers on the learning process at SDN 04 Karangtengah, Cibadak District, Sukabumi Regency. This study used a type of qualitative research where the subjects in this study were teachers and fourth grade students. Data collection was carried out by observation and interview techniques with research instruments in the form of observation sheets and interview sheets. The results showed that the provision of rewards and ice breakers had a very good impact on the learning process in class IV SDN 04 Karangtengah. Thus it can be concluded that giving rewards and ice breakers is able to arouse student learning motivation so that it also has an impact on cognitive learning outcomes. Giving rewards and ice breakers can bring out the enthusiasm of students in learning, learning becomes more competitive, collaborative, and varied so that students return to concentrate and actively participate in learning.